Changing Skill Formation in Greece and Italy – Crisis-Induced Reforms in Light of Common Institutional Legacies - Baumann, Fabienne-Agnes; Vossiek, Janis (International Journal for Research in Vocational Education and Training, 2022)
Context: After the Eurozone crisis unfolded a decade ago, comparative political economy has investigated reforms of public administration, labour market, welfare state and economic policy particularly in Southern European nations which were hit hardest by the crisis. However, analyses of skill formation reform, particularly vocational education and training (VET), have been scant, despite a common problem pressure for reforms emanating from stubbornly high rates of youth unemployment and similar legacies of statist VET. Approach: We investigate VET reforms brought underway in Greece and Italy during and in the aftermath of the crisis, asking how far apprenticeship-like forms of learning within their VET systems were strengthened. Empirically, we base our analysis on primary and secondary sources, having conducted semi-structured expert interviews in Greece and Italy in 2019. Results: We find that both countries attempted to strengthen the role of apprenticeship and work-based learning, but that politics differed across the two cases in the context of the Eurozone crisis. While in Italy, reforms were 'internalised' and shaped by domestic politics, Greek reforms were largely driven exogenously by the negotiations with the Troika. Conclusion: Although Italy and Greece have undertaken reforms to reduce the dominance of the state in VET provision by expanding apprenticeships and work-based learning, these do not amount to large scale changes to the dominant logic of school-based VET provision. In order to boost their potential in terms of practical learning both countries would need to continue on their reform pathways.